KETIKA IZIN PENGADILAN DIABAIKAN: Studi tentang Konflik Poligami antara Praktik Sosial dan Norma Hukum Keluarga Islam - Muhamad Andriyanto; Muhamad Fauzi Manarul Hidayah (PT Taskuliah Edukasi Indonesia, 2025)
Polygamy is permitted under Islamic law under certain conditions, including obtaining permission from the first wife and the Religious Court, as stipulated in the Marriage Law and the Compilation of Islamic Law (KHI). However, in practice, there are many cases of polygamy that do not comply with these legal requirements, which has implications for the validity of the marriage and the protection of women's rights. This study aims to analyze the legal consequences of practicing polygamy without permission in the Religious Court from the perspective of Islamic family law. This is a literature review study analyzing relevant legal literature and documents. The findings of the study indicate that polygamy without permission can be legally annulled and give rise to legal liability, including compensation to the first wife and fulfillment of the child support rights from the annulled marriage. The Religious Court plays a key role in verifying the wife's consent, the husband's ability to be fair, and determining the validity of the second marriage. In conclusion, the practice of polygamy that does not follow legal procedures demonstrates the weak legal awareness of the perpetrators and the need to strengthen the role of religious courts in upholding the principles of justice and the protection of women. Contribution: Theoretically, this study enriches the study of Islamic family law, particularly in the practice of polygamy without permission, to ensure justice and legal certainty. [ Poligami dalam hukum Islam diperbolehkan dengan syarat-syarat tertentu, termasuk memperoleh izin dari istri pertama dan Pengadilan Agama, sebagaimana diatur dalam Undang-Undang Perkawian dan Kompilasi Hukum Islam (KHI). Namun, dalam praktiknya, tidak sedikit kasus poligami dilakukan tanpa memenuhi ketentuan hukum tersebut, yang berimplikasi pada keabsahan pernikahan dan perlindungan hak perempuan. Penelitian ini bertujuan untuk menganalisis konsekuensi hukum dari praktik poligami tanpa izin di Pengadilan Agama dalam perspektif hukum keluarga Islam. Penelitian ini merupakan studi kepustakaan dengan menganalisis literatur dan dokumen hukum yang relevan. Temuan penelitian menunjukkan bahwa poligami tanpa izin dapat dibatalkan secara hukum dan menimbulkan tanggung jawab hukum, termasuk pemberian kompensasi kepada istri pertama serta pemenuhan hak nafkah anak dari pernikahan yang dibatalkan. Pengadilan agama memainkan peran kunci dalam memverifikasi persetujuan istri, kemampuan suami berlaku adil, serta memutus keabsahan pernikahan kedua. Kesimpulannya, praktik poligami yang tidak mengikuti prosedur hukum menunjukkan lemahnya kesadaran hukum pelaku dan perlunya penguatan peran pengadilan agama dalam menegakkan prinsip keadilan dan perlindungan perempuan. Kontribusi: Secara teoritis, penelitian ini memperkaya kajian hukum keluarga Islam khussunya dalam praktik poligami tanpa izin guna menjamin keadilan dan kepastian hukum].